PENGARUH GOOD CORPORATE GOVERNANCE DALAM MEMPENGARUHI HARGA SAHAM PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012 - Lumban Toruan, Antonius Jogi Mamora (Jurnal Akuntansi AKUNESA, 2014)
Purpose of this study was to determine the effect of corporate governance on the level of share prices of banking companies listed on the Stock Exchange in 2012, in particular through the measurement of institutional ownership and blockholder. This study uses quantitative research using secondary data is data banking company's financial statements in 2012. the results of this study indicate a significant difference due to the implementation of good corporate governance. in addition, institutional ownership and blockholder is used as a measuring device also provides a positive and significant effect.Keyword : good corporate governance, institusional ownership, blockholder